THE EFFECT OF SEED SPROUTING DAMAGE ON FIELD EMERGENCE AND YIELD OF SPRING TRITICALE - Maria MOŚ; Tomasz WÓJTOWICZ (Journal of Central European Agriculture, 2005)
In the years 1999-2001 two-factor fi eld experiments were carried out in which the effects of spring triticale seed sprouting damage on fi eld emergence, elements of the structure of yield and the yield were investigated. The research covered three cultivars: Gabo, Migo and Wanad. The statistical analysis of the results showed signifi cant effects of years and sprouting damage on fi eld emergence in all the years. Consequently, these factors affected the number of spikes per unit area, weight of 1,000 seeds and the yield in the years which were unfavourable for emergence (1999, 2000). In those years the decrease in yield, in the case of seeds with the most severe sprouting damage, ranged from 29% to 65% as compared with the control. In the favourable year 2001, in spite of a signifi cant effect of seed sprouting damage on fi eld emergence, the emergence level was so high that no decrease in the investigated elements of the structure of yield and the yield was observed.